Lisboetas . The Lisboners - Trefaut, Sergio (ICAM - Portuguese Film Institute, 2004)
Duration: 00:58:00 Lisboetas focuses on a new wave of immigrants from Brazil, Eastern Europe and Africa currently changing the face of a capital that used to be a point of departure and is now seen by many foreigners as a land of opportunity. But who are these new Lisboetas, then? Thirty-one year-old Tréfaut traces a portrait of them, opening a cinematic window onto these people's family lives, work, religious rituals and civil rights. Building a bridge between cinema and contemporary art, Tréfaut had already developed a 30-minute video installation called "Novos Lisboetas", shown in the Parc La Villette (Paris) in 2003, which can currently be seen in the Calouste Gulbenkian Foundation (Lisbon).